Petrographic study of rocks in The Julu Rayeu Formation and the Center of the Geureundong Volcanic in Nisam District, North Aceh District, Aceh Province - Dewi Sartika; Millati Amalia Sentosa; Fahri Adrian; Akmal Muhni; Dina Gunarsih; Hidayat Syah Putra; Rifqan Rifqan (PSI-Aceh, 2023)
Abstrak. Berdasarkan kondiri geologi, Kecamatan Nisam berada pada Formasi Julu Rayeu dan Batuan Pusat Gunungapi Geureundong. Litologi yang terdapat pada Formasi Julu Rayeu terdiri atas endapan sungai, batupasir tufaan, lempung berlignit, sedangkan litologi pada Batuan Pusat Gunungapi Geureundong yaitu Breksi Andesit. Metode yang digunakan pada penelitian ini meliputi metode pemetaan geologi dan analisis petrografi. Penelitian ini bertujuan untuk mengetahui kondisi geologi dan komposisi mineral penyusun batuan pada daerah penelitian. Berdasarkan hasil penelitian yang telah dilakukan diperoleh kondisi geologi yaitu litologi terdiri dari 4 satuan batuan meliputi batupasir, batupasir tufaan, batulempung, dan endapan kolovium. Hasil analisis petrografi pada batuan beku menurut klasifikasi IUGS (1973) terdiri dari 4 sampel yaitu AU12, AU41, AU72 dan AU73 disebut Andesit, sedangkan batupasir berdasarkan klasifikasi Pettijohn (1975) terdiri dari dua sampel yaitu AU32 dan AU62 disebut Lithic Greywacke. Abstract. Based on geological conditions, Nisam District is located in the Julu Rayeu Formation and the center of the Geureundong Volcanic. The lithology found in the Julu Rayeu Formation consists of river deposits, tuffaceous sandstones, and lignite clays, while the lithology of the central rocks of the Geureundong volcano is andesite breccia. The methods used in this study include geological mapping methods and petrographic analysis. This study aims to determine the geological conditions and constituent mineral composition of the rock in the study area. Based on the results of the research that has been carried out, the geological conditions are obtained, namely lithology consisting of 3 rock units including sandstone, tuffaceous sandstone, claystone, and colluvium deposits. The results of petrographic analysis on igneous rocks according to the IUGS classification (1973) consist of 4 samples namely AU12, AU41, AU72, and AU73 called Andesite, while sandstones based on Pettijohn’s classification (1975) consist of two samples namely AU32 and AU62 called Lithic Greywacke.